FACTORS ASSOCIATED WITH MENSTRUAL HYGIENE MANAGEMENT PRACTICES AMONG SECONDARY SCHOOL GIRLS IN LIRA SUBCOUNTY LIRA CITY WEST. - Margret Nakaweesi (Student's Journal of Health Research Africa, 2023)
Background: